2012
DOI: 10.5897/ajpp12.658
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Panax ginseng against N-acetyl-p-aminophenol-induced hepatotoxicity in rats

Abstract: Panax ginseng (PG) has been commonly used as medicinal herb for the treatment of various diseases in Eastern Asia for thousands of years. This study was designed to investigate the protective effect of PG against paracetamol-(N-acetyl-p-aminophenol; APAP)-induced liver damage in rats. Thirty-two albino Wistar rats were divided into four groups: Group C (control); Group APAP (gavaged orally with APAP (APAP, 2 g/kg, single dose); Group PG 100 mg/kg + APAP or 200 mg/kg + APAP (these two groups were treated by gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…SV for 21 days and paracetamol in the last 4 days resulted in a significant increase in serum AST, ALT, ALP, and total bilirubin levels and significant decrease in serum albumin and total protein levels associated with significant increase in liver MDA, TNF‐α, Caspase‐3 and significant decreased liver SOD, GPx, and GSH. These results are in agreement with Knight et al., Uzkeser et al., Hassanin et al., Alantary et al., and Enogieru et al . who found that paracetamol resulted in elevation of liver enzymes and increased MDA level, lipid peroxidation, and elevation of TNF‐α.…”
Section: Discussionsupporting
confidence: 92%
“…SV for 21 days and paracetamol in the last 4 days resulted in a significant increase in serum AST, ALT, ALP, and total bilirubin levels and significant decrease in serum albumin and total protein levels associated with significant increase in liver MDA, TNF‐α, Caspase‐3 and significant decreased liver SOD, GPx, and GSH. These results are in agreement with Knight et al., Uzkeser et al., Hassanin et al., Alantary et al., and Enogieru et al . who found that paracetamol resulted in elevation of liver enzymes and increased MDA level, lipid peroxidation, and elevation of TNF‐α.…”
Section: Discussionsupporting
confidence: 92%
“…Until now, although the exact mechanisms underlying APAP-induced hepatotoxicity remain unclear, growing evidence indicates that multiple mediators of inflammation and oxidative stress contribute to the pathology process of APAP-induced acute liver damage [6]. These inflammatory mediators include tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-10 (IL-10), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with nobiletin decreased the levels of proinflammatory cytokines, such as TNF‐α, IL‐1β, and IL‐6, compared with the APAP group. TNF‐α is one of the major proinflammatory cytokines that mediate acute phase responses causing various liver and kidney toxicities, such as APAP . Among the types of inflammatory damage affecting visceral organs, IL‐1β is one of the earliest proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%